Two new species of Cerogamasus Jin & Yao, 2024 (Acari, Parasitiformes, Parasitidae) from China - Yao, Mao-Yuan; Ren, Rong; Chen, Jian-Xin; Wu, You-Fang; Yi, Tian-Ci; Jin, Dao-Chao (Zootaxa, 2026)
During a survey of Chinese Parasitidae, two new species, Cerogamasus cornutus Ren & Yao sp. nov. and Cerogamasus crassipilosus Ren & Yao sp. nov., were discovered and described. A new key to females of the known species of the genus is presented.